2022
DOI: 10.1186/s42269-022-00783-3
|View full text |Cite
|
Sign up to set email alerts
|

Screening of Manilkara zapota (L) P. Royen stem bark ethanolic extract for in vitro α-glucosidase inhibition, preliminary antidiabetic effects, and improvement of diabetes and its complications in alloxan-induced diabetes in Wistar rats

Abstract: Background A perusal of the literature suggested that Manilkara zapota (L.) P. Royen stem bark (MZSB) is enriched with several bioactive phytoconstituents but had not been yet screened for its in vitro and in vivo antidiabetic potentials. Thus, the present study aimed to investigate the effects of 70% ethanolic extract of Manilkara zapota (L) P. Royen stem bark (EMZSB) in DPPH- and H2O2-scavenging assay, in vitro α-glucosidase inhibition assay, ameliorating diabetes and its complications in all… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(2 citation statements)
references
References 78 publications
1
1
0
Order By: Relevance
“…The current study's preliminary phytochemical analysis of the ethanolic extract revealed the presence of carbohydrates, flavonoids, steroids, anthraquinone glycosides, tannins, and phenolic compounds. This finding was consistent with earlier literature, which also revealed the presence of anthraquinone glycoside, amino acids, proteins, saponin, gums, reducing sugars, tannins, and flavonoids (Karle et al, 2022).…”
Section: Figuresupporting
confidence: 94%
“…The current study's preliminary phytochemical analysis of the ethanolic extract revealed the presence of carbohydrates, flavonoids, steroids, anthraquinone glycosides, tannins, and phenolic compounds. This finding was consistent with earlier literature, which also revealed the presence of anthraquinone glycoside, amino acids, proteins, saponin, gums, reducing sugars, tannins, and flavonoids (Karle et al, 2022).…”
Section: Figuresupporting
confidence: 94%
“…Therefore, inhibition of alpha-glucosidase is an effective strategy to control hyperglycemia [ 13 ]. Commercially, acarbose (Glucobay) and miglitol (Glyset) are famous alpha-glucosidase inhibitors, but daily consumers of these drugs complain of bloating, diarrhea and flatulence, leading to loss of appetite [ 14 , 15 , 16 , 17 , 18 ]. To overcome these side effects, it is crucial to explore new alpha-glucosidase inhibitors with better inhibition potency and minimal side effects.…”
Section: Introductionmentioning
confidence: 99%